EVALUASI KEBERHASILAN PROGRAM PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) DI KABUPATEN TEGAL (Kajian Peraturan Bupati No. 50 Tahun 2010 Tentang Petunjuk Pelaksanaan Bantuan Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat - Ilham Tegar Faza; Sri Suwitri (Journal of Public Policy and Management Review, 2017)
Success Evaluation Program for Water Supply and Sanitation is a community based program to meet the needs of local communities in need of clean water and sanitation are maintained and made independently from both government and the public and private sectors. The purpose of this study to analyze the PAMSIMAS program evaluation in the implementation and improvement effort against obstacles PAMSIMAS program through performance indicator targets of the program. This program evaluation factors concerning the implementing organizations, programs, and beneficiaries while efforts to improve the program's success factors regarding the organization's decision-making process, the requirements of the task and authority, the competence of the executive staff, the expression of the demands. The results of the study Evaluation of Success Program for Water Supply and Sanitation Community Based in Tegal regency, there are still constraints on some aspects like implementing organizations with the beneficiaries, should their relationships and communications between managers of both government and society to better public awareness for clean water still less.